Employing the PERT Method in Planning Academic Leadership Training Programs in Saudi Universities in Light of Digital Transformation - Amani Awaji (Umm Al-Qura University, 2022)
The study aimed to reveal the role of employing the PERT method in planning academic leadership training programs in Saudi universities. The PERT method was also applied in the aspect of time and cost on EXCEL software, one of PERT's computer software, in planning a training program for academic leaders in Saudi universities with the aim of ensuring its implementation in the least time and lowest cost and achieving the highest possible efficiency and quality. Whereas, the PERT method was employed in the technical aspect of time and cost in planning a training program for academic leaders in Saudi universities to ensure its implementation in the least time and lowest cost and to achieve the highest possible efficiency and quality. To achieve this, the descriptive approach was used, and the most prominent findings of the study were that the total time estimated to plan the training program according to Bert is (18) days and at a cost of 2670, unlike what was traditionally planned at (20) days and the cost of (3000), as well as Bert's applied steps showed that the possible paths on the network for the program application steps amounted to 3 paths. Path (C) represents the critical path for taking longer in implementation. There is many technical software that enable decision makers based on planning training pro-grams to reduce the duration of preparing a program plan with the least percentage. There are mistakes, especially in large training programmers, and the study recommended the need to work on employing scientific methods in planning the completion of training programs approved by universities, because the use of these methods achieves effective results in reducing time and cost.